2019
DOI: 10.1038/s41379-018-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

CD30 expression in neoplastic T cells of follicular T cell lymphoma is a helpful diagnostic tool in the differential diagnosis of Hodgkin lymphoma

Abstract: Follicular T cell lymphoma is derived from follicular T-helper cells. In many cases, neoplastic T cells form rosettes around Hodgkin-Reed-Sternberg-like cells, which can lead to the misdiagnosis of classical Hodgkin lymphoma. The aim of the present study was to obtain a better understanding of this rosetting phenomenon and to recognize features that are helpful in the differential diagnosis of classical Hodgkin lymphoma. Sixteen mostly elderly follicular T cell lymphoma patients (mean 66 years) were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…4). 48,52 One study found that the neoplastic cells had at least partial expression of CD30 in 75% of their case series. 52 A component of large blastic EBV-positive or -negative B cells is often identified, frequently with RS-like morphology and immunophenotype ( Fig.…”
Section: Follicular T-cell Lymphoma (F-ptcl)mentioning
confidence: 99%
See 2 more Smart Citations
“…4). 48,52 One study found that the neoplastic cells had at least partial expression of CD30 in 75% of their case series. 52 A component of large blastic EBV-positive or -negative B cells is often identified, frequently with RS-like morphology and immunophenotype ( Fig.…”
Section: Follicular T-cell Lymphoma (F-ptcl)mentioning
confidence: 99%
“…4). 24,48,52,53 A chromosomal translocation t(5;9)(q33;q22) involving ITK and SYK tyrosine kinases is found in about 20% of F-PTCL, and has been reported thus far in only one case of typical AITL. 48,54,55 The ITK-SYK fusion may be detected by fluorescence in situ hybridisation (FISH) assays, but its diagnostic value is rather limited.…”
Section: Follicular T-cell Lymphoma (F-ptcl)mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, a relatively high frequency of Tfh cells co-expressing CXCR5 and CXCL13 was found in AITL compared to tonsils, suggesting an important role for the CXCR5/CXCl13 axis as regulator of the Tfh cell trafficking and positioning in AITL LNs. CD30, a receptor found on activated T cells and widely used for diagnosis of peripheral T lymphomas (61,62,94), was readily found in AITL Tfh cells but it was almost absent in their tonsillar counterparts. Interestingly, the majority of CD30 hi Tfh cells were expressing a BCL6 hi phenotype too, indicating a possible role of CD30 in the differentiation process of AITL Tfh cells.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5% of non-T cells in the tumor area were CD30+. Interestingly, a relatively high frequency of Tfh cells were positive for CD30, a receptor often found in AILT (61)(62)(63), in LNs (36%) while normal Tfh cells in tonsil GC very rarely coexpressed CD30 (0.04%) (Table 4). Analysis of the three aforementioned Tfh cell signatures revealed a different pattern in AITL compared to tonsils (Figure 5B).…”
Section: Different Tfh Core Signatures Between Tonsillar and Neoplastic Lymph Node Tissuesmentioning
confidence: 99%